Perancangan Logo Kampanye Sosial Bahaya Gerd Untuk Remaja Usia 18-24 Tahun - Alfredy Mushowiru; Aditya Rahman Yani; Mahimma Romadhona (CV. ULIL ALBAB CORP, 2024)
Modern lifestyles that tend to be practical and instant contribute to an increased risk of disease, including Gastroesophageal Reflux Disorder (GERD). Based on previous studies, unhealthy diets, lack of physical activity, and bad habits are the main triggers for GERD. Most teenagers have an unhealthy lifestyle. Research obtained through distributed questionnaires found that 64.2% of 81 teenagers aged 18-22 years stated that they often consumed spicy, fatty, or sour foods. As an effort to raise awareness about the dangers of GERD, this campaign was designed to provide education about the dangers of GERD. In designing this campaign, a strong visual identity, including a logo, is an important element to attract the attention of the audience. It is hoped that this campaign can have a positive impact in educating teenagers to maintain a healthy lifestyle and prevent GERD.)